A robust and effective framework for 3D scene reconstruction and high-quality rendering in nasal endoscopy surgery - Ji, Xueqin; Zhao, Shuting; Liu, Di; Wang, Feng; Chen, Xinrong (Frontiers in Neurorobotics, 2025)
In nasal endoscopic surgery, the narrow nasal cavity restricts the surgical field of view and the manipulation of surgical instruments. Therefore, precise real-time intraoperative navigation, which can provide precise 3D information, plays a crucial role in avoiding critical areas with dense blood vessels and nerves. Although significant progress has been made in endoscopic 3D reconstruction methods, their application in nasal scenarios still faces numerous challenges. On the one hand, there is a lack of high-quality, annotated nasal endoscopy datasets. On the other hand, issues such as motion blur and soft tissue deformations complicate the nasal endoscopy reconstruction process. To tackle these challenges, a series of nasal endoscopy examination videos are collected, and the pose information for each frame is recorded. Additionally, a novel model named Mip-EndoGS is proposed, which integrates 3D Gaussian Splatting for reconstruction and rendering and a diffusion module to reduce image blurring in endoscopic data. Meanwhile, by incorporating an adaptive low-pass filter into the rendering pipeline, the aliasing artifacts (jagged edges) are mitigated, which occur during the rendering process. Extensive quantitative and visual experiments show that the proposed model is capable of reconstructing 3D scenes within the nasal cavity in real-time, thereby offering surgeons more detailed and precise information about the surgical scene. Moreover, the proposed approach holds great potential for integration with AR-based surgical navigation systems to enhance intraoperative guidance.